Green hydrogen revolution in aviation: requirements and possibilities - Janjua, Shahzada Sulman (Cranfield University, 2023)
This work investigates the case for sustainable aviation for the Asia Pacific region and focusses on Hong Kong. Hong Kong presently generates 50% of its energy from coal. The aim is to remove carbon from aviation fuels for Hong Kong and replace it with green hydrogen. This is a viable choice of sustainable aviation fuel but switching it from kerosene would require the overcoming of some challenges. This thesis comprises of three parts: firstly, the modelling and simulation of the Trent-XWB-97 jet engine as a baseline combusting Jet-A fuel. Its aircraft performance is then compared to a cryogenically fuelled green hydrogen engine. Secondly, the reference engine is then fitted with an intercooler with the gain of aircraft performance benefits in mind as well as to utilise it as a heat exchanger to vapourise the liquid hydrogen and thirdly, large-scale green hydrogen production using renewables is envisaged as part of a Green Hydrogen Hub network encompassing a green hydrogen logistical supply chain paving the way for a future aviation hydrogen micro-economy. It was discovered that relative to the Jet-A fuelled engine, the engine with a constant net thrust for ODP (Take-Off) and DP (Cruise) conditions decreased the ESFC for both baseline and intercooled engines. For the reference case at ODP this drop in ESFC was (1.71%) and (1.3%) for the intercooled scenario. There was also an accompanying decrease in TET; for the baseline engine this was 47K and for the intercooled engine this was 50K. The addition of the intercooler achieved the greater aircraft thrust requirement of 448kN and also vapourised the cryogenic hydrogen to high enough temperatures. These were calculated to be 536K and 296K for the ODP and DP respectively. The results showed that the baseline engine carried the greatest payload of 31866 kg with a block fuel burn of 36267 kg and a flight duration of 11.83 hours. The intercooled engine yielded a maximum carried payload of 27184 kg and the block fuel burn was 43349 kg and a flight time of 11.97 hours. The study also discovered that the 43.4 tonnes of green hydrogen can be generated in Hong Kong using wind and solar power and that its usage reduced the civil aviation carbon footprint of Hong Kong by 11.6%.
Pilidis, Pericles - Associate Supervisor
Keywords: Green hydrogen; Turbomatch; Trent-XWM-97; aircraft performance; Hong Kong.; Asia Pacific